Supervision Strategy in Improving Teacher Quality at Universitas Islam As-Syafi’iyah - Sri Lestari; Ma’ruf Akbar; Budi Santoso (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
Teacher’s quality has a great influence on the success of achieving educational goals. Therefore, the teacher’s quality must be improved through an appropriate supervisory strategy. The purpose of this study was to determine the supervision strategy in improving the quality of teachers at Universitas Islam As-Syafi’iyah. The method used descriptive qualitative. Data collecting techniques were interviews and documentation. Data were analyzed by using three stages: data reduction, data exposure and analysis, and drawing conclusions. The results showed that the supervisory strategy undertaken was the procurement of Mendeley training activities, training in the use of sisters and syllables, teaching and learning seminars, further studies, scholarships, evaluating teacher’s performance and auditing activities in stages and regularly. It had implications for the performance of teachers so that the learning process and teaching become more quality. Thus, educational goals that have been set can be achieved. Keywords: Supervision Strategy, Teacher Quality, Performance Quality